Coronary artery disease and restenosis after peripheral endovascular intervention are predictors of poor outcome in peripheral arterial disease. Issue 7 (14th October 2020) - Favaretto, Elisabetta; Sartori, Michelangelo; Pacelli, Antonio; Conti, Eleonora; Cosmi, Benilde
Abstract: Background: Few data are available on long-term atherothrombotic events after percutaneous transluminal angioplasty (PTA) for peripheral arterial disease (PAD). Restenosis after PTA may be a marker of a more aggressive atherothrombosis. Aim: To ascertain whether restenosis detected by duplex sonography (DUS) after PTA for iliac and femoro-popliteal disease is associated with a higher risk of cardiovascular events. Methods: We conducted a prospective cohort study of patients undergoing iliac or femoro-popliteal PTA for PAD. Patients were seen at one month, six months, one year and every year thereafter after PTA. At each visit, DUS was performed and accordingly restenosis was stratified into two categories (absent/present). The outcome was the composite of major adverse cardiovascular events (MACE). Results: Two hundred and fifty patients (aged 69 ± 11 years, male 59.2%) were enrolled. During a mean follow-up of 1207 ± 904 days, 102 (40.8%) patients developed restenosis. Restenosis was more frequent in patients with diabetes and critical limb ischaemia. MACEs ( n  = 76) were more frequent in the patients that developed restenosis vs. those that did not (40.2 vs. 23.6%, p  = .005). Predictors of MACEs were diabetes (HR 2.02, 95%CI: 1.19–3.41, p  = .009), presence of coronary heart disease at enrolment (HR 2.84, 95%CI: 1.78–4.53, p  = .001) and restenosis (HR 1.87, 95%CI: 1.16–3.00, p  = .010). Conclusion: Restenosis at DUS, diabetes, and coronary heart disease in patients who underwent iliac or femoro-popliteal PTA for PAD are associated with increased risk of arterial thrombotic event. Intervention trials are required to show the benefit of different therapeutic approaches in such patients at high risk of clinical deterioration.